Caveolin-1 in the regulation of cell metabolism: a cancer perspective. Issue 1 (December 2016) - Nwosu, Zeribe; Ebert, Matthias; Dooley, Steven; Meyer, Christoph
Abstract Caveolin-1 (CAV1) is an oncogenic membrane protein associated with endocytosis, extracellular matrix organisation, cholesterol distribution, cell migration and signaling. Recent studies reveal that CAV1 is involved in metabolic alterations – a critical strategy adopted by cancer cells to their survival advantage. Consequently, research findings suggest that CAV1, which is altered in several cancer types, influences tumour development or progression by controlling metabolism. Understanding the molecular interplay between CAV1 and metabolism could help uncover druggable metabolic targets or pathways of clinical relevance in cancer therapy. Here we review from a cancer perspective, the findings that CAV1 modulates cell metabolism with a focus on glycolysis, mitochondrial bioenergetics, glutaminolysis, fatty acid metabolism, and autophagy.